Research Progress of ROS-Mitochondrial Pathway on Cardiovascular Protection of Tea Polyphenols - Tingting DENG; Jinchan PI; Xiaoping PENG; Yufei YAO; Yiquan LI; Wenjuan LI (Shipin gongye ke-ji)
Reactive oxygen species (ROS) imbalance and mitochondrial dysfunction played critical roles in the pathogenesis of cardiovascular diseases which are the leading cause of death worldwide. Mitochondrion is the main ROS production, which is also the vulnerable target for ROS attack. Compelling evidence has been provided that tea polyphenols could regulate ROS generation and protect mitochondrial structure and function, contributing to its beneficial health effects on cardiovascular protection. Hence, the article introduces the sources and detrimental effects of ROS, then the intrinsic connections between ROS, mitochondria, and the development of cardiovascular diseases, as well as the ROS-scavenging effects of tea polyphenols are summarized. From the perspective of ROS-mitochondrial pathway, the article elucidates how tea polyphenols behaved the beneficial effects against cardiovascular diseases by modulating the expression of mitochondrial fusion and fission proteins, reducing the opening of mitochondrial membrane permeability transition pore, maintaining cellular calcium homeostasis, mitigating mitochondrial DNA damage and regulating mitochondrial apoptosis signaling pathways. Correspondingly, the potential applications of tea polyphenols are discussed, aiming to provide valuable insights for research and application in related fields.